Modelling dependance in collateralied debt obligations with copulas - Linley, Christopher (Department of Mathematics and Applied Mathematics, 2014)
In this paper we provide a review of credit derivatives, and some of the tools used to model them. We give a basic introduction to copulas and how they are used to model the depedence between single name credit derivatives. We then investigate various features of Gaussian and t copula dependence using numerical results obtained from Monte-Carlo simulation.